System of environmental-economic accounting 2012 : experimental ecosystem accounting. - United Nations Committee of Experts on Environmental-Economic Accounting (New York : United Nations, 2014)
Reflects a synthesis of the current knowledge in the area and provides a starting point for the development of ecosystem accounting at national and sub-national levels. It represents a strong and clear convergence across the disciplines of ecology, economics and statistics on many core aspects related to the measurement of ecosystems.
"The United Nations Committee of Experts on Environmental-Economic Accounting managed and coordinated the work"--p. iii.
"United Nations Sales no.: E.13.XVII.13"--Title page verso.
"European Union catalogue no. KS-05-14-103-EN-C ; catalogue no. KS-05-14-103-EN-N"--Title page verso.
Produced and is released under the auspices of the United Nations, the European Commission, the Food and Agriculture Organization of the United Nations, the Organisation for Economic Co-operation and Development and the World Bank Group.
Keywords: Biotic communities -- Accounting; Environmental auditing; National income -- Accounting